Associations of metabolic dysfunction-associated fatty liver disease and hepatic fibrosis with bone mineral density and risk of osteopenia/osteoporosis in T2DM patients - Zhang, Wei; Li, Yuhua; Li, Shangjian; Zhou, Jingqi; Wang, Kai; Li, Zhibin; Chen, Ning; Chen, Xueqin (Frontiers in Endocrinology, 2023)
Background: Existing evidence on associations of liver steatosis and fibrosis with bone mineral density (BMD) and risk of osteopenia /osteoporosis was limited with conflicting results. We aimed to evaluate associations of metabolic dysfunction-associated fatty liver disease (MAFLD) and hepatic fibrosis with BMD and risk of osteopenia/osteoporosis in type 2 diabetes mellitus (T2DM) patients.Methods: Baseline information of an ongoing cohort of 249 T2DM patients in Xiamen, China were analyzed. MAFLD was defined as the presence of hepatic steatosis (diagnosed by either hepatic ultrasonography scanning or fatty liver index (FLI) score >60) for T2DM patients. BMD was measured using dual-energy X-ray absorptiometry at total lumbar (L2-4), femur neck (FN), and total hip (TH) and was categorized as normal (T ≥ -1.0), osteopenia (-2.5 < T < -1.0) or osteoporosis (T ≤ -2.5) according to its minimum T-score.Results: Among the 249 T2DM patients, prevalence rates of MAFLD, osteopenia and osteoporosis were 57.8%, 50.6% and 17.7%, respectively. Patients with MAFLD had significantly higher BMD T-scores of L2-4, FN, TH and the minimum as well as lower prevalence of osteoporosis than patients without MAFLD. Hepatic steatosis indices, including FLI score, fatty liver (FLI>=60 or hepatic ultrasonography scanning) and MAFLD, were significantly and positively, while hepatic fibrosis index, FIB-4 score, but not NAFLD fibrosis score (NFS), was negatively, associated with all T-scores. MAFLD was significantly associated with decreased risk of osteopenia/osteoporosis and osteoporosis with the unadjusted odds ratios (ORs) (95%CI) of 0.565 (0.324-0.987) and 0.434 (0.224-0.843) (both p-values<0.05), respectively. As for liver fibrosis, FIB-4 score, but not NFS, was significantly associated with elevated risk of osteoporosis with unadjusted OR (95%CI) of per SD increase of FIB-4 score of 1.446 (1.080-1.936, p-value=0.013). With adjustment for potential confounding variables, especially body mass index, in the multivariable regression analyses, all associations of hepatic steatosis and fibrosis indices with BMD and risk of osteopenia/osteoporosis were not statistically significant.MAFLD and hepatic fibrosis were not significantly associated with BMD and risk of osteopenia/osteoporosis independent of obesity. Nevertheless, screening and management of MAFLD and osteopenia/osteoporosis were still important for prevention of fracture in T2DM patients.